LYING HONESTLY FOR GOVERNMENT: LINGUISTIC MANIPULATION AS DISINFORMATION STRATEGY IN NIGERIA - Agbedo, Christopher Uchenna; Krisagbedo, Ebere Celina (Innovare Journal of Social Sciences, 2014)
This paper examines the state hallowed art of disinformation and its implications for good governance in Nigeria. It focuses on the practised art of telling lies honestly by government spokespersons and media aides in the course of discharging their public relations duties for their principals. The database is the issue of disinformation surrounding the health challenges of Dame Patience Jonathan (wife of President Goodluck Jonathan) and Sullivan Chime (Governor of Enugu State) elicited from the Nigerian media. The result of the data analysis reveals deliberate efforts by government spokespersons to engage the reverse gear of disinformation willfully intended to manipulate the Nigerian audience at the rational level by either discrediting conflicting information or supporting false conclusions. A common disinformation thread that ran through this ‘statutory' practice was the tendency to mix some truth and observations with false conclusions and ‘honest' lies or to reveal part of the truth while presenting it to the discerning public as the whole. Contrary to the dictates of this war of disinformation into which the media relations managers conscripted themselves to dictate the very form and existence of the truth and allow it to drift, obscured in a thick fog of contrivance, Mrs. Jonathan and Governor Chime returned from their long medical sojourn to spill the beans about their health challenges. It hardly occurred to the spin doctors that lies have slender and fragile frames that break too soon and therefore require constant attentiveness to keep them alive. The exposure of a single truth about their medical tourism ripped through a web of lies dexterously woven by the public relations handlers, pulverizing it instantly and thus, investing government with the inglorious toga of integrity deficit. The implication for governance is that the people no longer believe the government or the President because they have come to understand that the government does not tell the truth. The ignoble badge of credibility problem and integrity deficit, which the disinformation gamble of government's spokespersons has foisted on the federal government, is akin to the official deception over the war in Vietnam that caused a major erosion of confidence of the American people in their government. The disclosures of Mrs. Jonathan and Mr. Chime did demonstrate how easy it is for government officials to take recourse to disinformation to culture a system of institutionalized lying. The result of such institutionalized lying and official deception has been to shred the fabric of trust between people and government.